Contracted Semivowels in Old Khotanese - Hitch, Doug (Indo-Iranian journal, 2016)
This completes a study begun with ‘Contracted Diphthongs in Old Khotanese’ (2015b) of the contractions seen in the secondary declensions. Here are examined the phenomena of diphthong resolution, semivocalization and glide resolution. Metrical patterns in the great Buddhist poem known as The Book of Zambasta are used to reveal word structure not shown by the orthography. The diphthongs revealed in the earlier study, written CyV or CvV may resolve into CiyV (CäyV) or CuvV but keep the same metrical count. Oblique plural is recognized as a distinct grammatical category and it is shown how the oblique plural suffixes induce semivocalization rather than diphthongization. The orthographic sequences containing a semi-vowel, CyV or CvV, are identical to those containing a diphthong. They may also resolve orthographically to CiyV (CäyV) or CuvV, but with these resolved glides an extra mora is added to the metrical count. An explanation is offered for the unusual morphophonological behavior and metrical distribution of the IAP morpheme -yau. Many of the contraction processes may also be seen with verb stems ending in /i/ and /u/.